From below: the work experience of youths in low-income homes - Margarita Estrada; Julieta Sierra; Lourdes Salazar (Íconos)
In this paper the work experience of a group of adolescents that live in low-income homes in Mexico is analyzed. In order to do this, work is defined in an ample way that integrates the activities oriented towards generating income, such as the conditions of the reproduction of the domestic group. From this perspective and grounded in 74 case studies in 27 urban and rural localities in the country in 2017, this article studies the diversity of work experiences that these adolescents have lived. This article also focuses on the conditions in which household chores take place, farming activities, participation in commerce, and domestic services, among the most frequent. One of the findings indicates that the initial activities that introduced youths to the job market began in their childhood with other members of their home and consolidated in their adolescence. This research shows the distinct forms of socialization in work from childhood, the differences between the experiences of women and men, and the ways in which material dimensions are articulated, symbolic and imaginary, about work in everyday life.